Material Requirement Planning Information System: Prototype And Lead Time Analysis - Mikhael Billy Tanaga; Raymond Sunardi Oetama (Universitas Bina Darma, 2023)
In the pharmaceutical manufacturing industry, efficient and accurate production processes ensure quality products and meet customer demands. However, many companies still rely on manual systems, such as Microsoft Excel, which can lead to challenges and inefficiencies. The problems identified include a lack of integration between product data and manufacturing documents, error-prone manual data entry, document mix-ups, and time-consuming processes. The study aimed to design and implement a web-based material requirement planning system to address the challenges of a manual manufacturing system in a pharmaceutical company. The objectives were to improve integration, streamline production processes, and reduce lead time for enhanced operational efficiency. The study employed a prototyping approach to design and develop a web-based material requirement planning system. User feedback and requirements guided iterative design cycles, while User Acceptance Testing evaluated system performance and usability. The impact on operational efficiency was assessed by measuring lead time before and after implementation. The implemented web-based material requirement planning system successfully resolved integration issues, reduced manual data entry errors, and minimized document mix-ups within the pharmaceutical manufacturing company. User Acceptance Testing achieved a 100% average percentage. The lead time was improved from 207-251 minutes to 122-159 minutes, demonstrating enhanced operational efficiency.